1989
DOI: 10.1002/j.1460-2075.1989.tb03469.x
|View full text |Cite
|
Sign up to set email alerts
|

Maize streak virus genes essential for systemic spread and symptom development

Abstract: The entire genome of single component geminiviruses such as maize streak virus (MSV) consists of a single‐stranded circular DNA of ~2.7 kb. Although this size is sufficient to encode only three average sized proteins, the virus is capable of causing severe disease of many monocots with symptoms of chlorosis and stunting. We have identified viral gene functions essential for systemic spread and symptom development during MSV infection. Deletions and gene replacement mutants were created by site‐directed mutagen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
1
2

Year Published

1991
1991
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(78 citation statements)
references
References 27 publications
(42 reference statements)
2
73
1
2
Order By: Relevance
“…Systemic infection by geminiviruses with bipartite genomes is not severely affected by disruption of their CP genes (Brough et al, 1988;Etessami et al, 1989). Where studied, geminiviruses with a single genomic DNA have no capacity to cause disease in the absence of the CP (Lazarowitz et al, 1989;Boulton et al, 1989;Briddon et al, 1989). Initial infection and movement of the TYLCV-Th A-DNA following agroinoculation is not completely eliminated by a mutation in the CP since systemic infection and mild symptoms occurred in whole plants, although delayed relative to infection by wild-type A-DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic infection by geminiviruses with bipartite genomes is not severely affected by disruption of their CP genes (Brough et al, 1988;Etessami et al, 1989). Where studied, geminiviruses with a single genomic DNA have no capacity to cause disease in the absence of the CP (Lazarowitz et al, 1989;Boulton et al, 1989;Briddon et al, 1989). Initial infection and movement of the TYLCV-Th A-DNA following agroinoculation is not completely eliminated by a mutation in the CP since systemic infection and mild symptoms occurred in whole plants, although delayed relative to infection by wild-type A-DNA.…”
Section: Discussionmentioning
confidence: 99%
“…The V 1 0 R F encodes a product of only 8-8K yet it may be functionally equivalent to the V 1 products encoded by other monopartite geminiviruses since computer analysis of hydrophobicity showed the presence of a hydrophobic N-terminal region which is conserved in other monocotinfecting geminiviruses (M. Boulton, unpublished data). The V1 product of MSV has been shown to be necessary for a symptomatic infection of maize plants (Boulton et al, 1989;Lazarowitz et al, 1989). A sequence analysis revealed that there was no possibility of the small ORF V1 of MiSV coding for a protein larger than 8.8K, it may represent the smallest functional protein identified in the geminiviruses, and may provide a caveat to the use of the 10K minimum size limit for the identification of potential gene products.…”
Section: A C-terminal Mutation Oforf Vomentioning
confidence: 99%
“…There is strong amino acid sequence and functional conservation among the AL1 and AL3 proteins encoded by geminiviruses with bipartite genomes (Howarth and Vandemark, 1989;Etessami et al, 1991;. This conservation also extends to the AL1 homologs encoded by geminiviruses with a single genome component (Mullineaux et al, 1985;Accotto et al, 1989;Lazarowitz et al, 1989;Schalk et al, 1989;Stanley et al, 1992). Three independent lines of evidence show that geminiviruses reproduce their circular, single-stranded DNA genomes by a rolling circle replication mechanism analogous to some prokaryotic viruses and plasmids.…”
Section: Introductionmentioning
confidence: 97%